CULTURAL ASPECTS IN LITERARY WORK as A REFLECTION OF HUMAN LIVES - Apriyanti, Chusna; Irawati, Iisrohli (MAGISTRA, 2015)
This paper in aimed to explain the culture aspects in literary work through three different kinds of literature (Indonesian literature, British literature, and American literature). The researcher uses descriptive qualitative research design. The data are collected by reading activities. The result shows that the aspects of human lives can be seen in cultural aspects of literary library work.